Suatu Kajian Tentang Bilangan Sempurna - Saiful Amri; Mahmudi Mahmudi (Journal of Data Analysis, 2019)
Dalam tulisan ini akan dijelaskan mengenai kriteria bilangan sempurna genap dan bentuk bilangan sempurna ganjil (jika ada). Jika $2^k-1$  prima maka $2^{k-1}(2^k-1)$  berupa bilangan sempurna. Sebaliknya, semua bilangan sempurna genap berbentuk $2^{k-1}(2^k-1)$ , dimana $2^k-1$ prima. Maka masalah menentukan bilangan sempurna genap setara dengan menentukan $k$ sehingga $2^k-1$  prima. Bilangan $2^k-1$ disebut sebagai bilangan Mersenne dan ditulis dengan $M_k$. In this paper will be explained about the criteria of the even perfect numbers and the form of odd perfect numbers (if any). If  is prime, then  is perfect. Conversely, all even perfect numbers are of the form  with  is a prime. Thus, finding even perfect numbers is equivalent to find the integers  for which  is prime. The numbers of the form  called Mersenne numbers and is denoted by .